2009
DOI: 10.1111/j.1439-0272.1981.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Seminal Biochemistry: Fructose, Ascorbic Acid, Citric Acid, Acid Phosphatase and their Relationship with Sperm Count

Abstract: The sperm count has been correlated with the concentration of different substances secreted by the adnexal glands with conflicting results.In order to assess their diagnostic significance in male infertility the following substances were measured in seminal plasma: fructose and ascorbic acid produced by seminal vesicles and acid phosphatase and citric acid by the prostate gland. A statistical evaluation was made with the data obtained from azoospermic, oligozoospermic and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Previously, Ishibe et al (1971) and reported that the leucine aminopeptidase activity decreases as sperm count declines. Similar correlation was observed by Jathar and Rashmi (1977) and Videla et al (1981) between sperm count and seminal plasma acid phosphatase activity which is known to be directly androgen dependent (Engberg et al -1974;Ostrowski -1980). Similar correlation was observed by Jathar and Rashmi (1977) and Videla et al (1981) between sperm count and seminal plasma acid phosphatase activity which is known to be directly androgen dependent (Engberg et al -1974;Ostrowski -1980).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previously, Ishibe et al (1971) and reported that the leucine aminopeptidase activity decreases as sperm count declines. Similar correlation was observed by Jathar and Rashmi (1977) and Videla et al (1981) between sperm count and seminal plasma acid phosphatase activity which is known to be directly androgen dependent (Engberg et al -1974;Ostrowski -1980). Similar correlation was observed by Jathar and Rashmi (1977) and Videla et al (1981) between sperm count and seminal plasma acid phosphatase activity which is known to be directly androgen dependent (Engberg et al -1974;Ostrowski -1980).…”
Section: Discussionsupporting
confidence: 77%
“…Present investigation however shows a significantly higher aminopeptidase activity in seminal fluid of non-obstructive azoospermic patients than that of other groups ( Table 2), suggesting an inverse relationship between aminopeptidase activity and sperm concentration. Similar correlation was observed by Jathar and Rashmi (1977) and Videla et al (1981) between sperm count and seminal plasma acid phosphatase activity which is known to be directly androgen dependent (Engberg et al -1974;Ostrowski -1980). The higher activity of acid phosphatase in non-obstructive azoospermic group is probably due to hyperplasia of testicular Leydig cell and increased androgen secretion (Phadke et al -1973).…”
Section: Discussionsupporting
confidence: 77%
“…The purpose of the studies is using seminal fructose test to replace percutaneous epididymis sperm aspiration (PESA) to diagnosis CBAVD. Fructose is essential for spermatozoa metabolism and spermatozoa motility [5]. Fructose is an energy source for spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Fructose is essential for spermatozoa metabolism and spermatozoa motility. 7 Fructose is an energy source for spermatozoa. It is produced by the seminal vesicles with some contribution from the ampulla of the ductus deferens.…”
Section: Introductionmentioning
confidence: 99%